Portraits of High Potential-High Need Students: The Role of Teacher Inquiry (LEARNing Landscapes, 2016)
This article examines inquiry-based instructional approaches to working with students who have high potential, but also special needs. The article focuses on inquiry as the thread that weaves together a plan of instruction that has been successful for these students across the high school years in one teacher’s classroom. Pro les of students are described with commentary as to the approaches employed with positive results. Commonalities of instruction, such as the use of metacognition, the use of acceleration, and the use of career counseling, are provided alongside student commentary where appropriate. A plan for the use of inquiry techniques in the classroom concludes the article.
Keywords: inquiry; special need; instruction; metacognition; commentary